2016
DOI: 10.1155/2016/2647389
|View full text |Cite
|
Sign up to set email alerts
|

A Self-Adaptive Fuzzyc-Means Algorithm for Determining the Optimal Number of Clusters

Abstract: For the shortcoming of fuzzy c-means algorithm (FCM) needing to know the number of clusters in advance, this paper proposed a new self-adaptive method to determine the optimal number of clusters. Firstly, a density-based algorithm was put forward. The algorithm, according to the characteristics of the dataset, automatically determined the possible maximum number of clusters instead of using the empirical rule n and obtained the optimal initial cluster centroids, improving the limitation of FCM that randomly se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 34 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…If clusters are too few, the algorithm would assign an artificially large area to the EZ defect, and vice versa, if clusters are too many, some pixels in the EZ defect area would be lost. Numerous methods have been proposed to solve this issue, such as evaluation of clustering quality by a validity index [47] based on either the degree of separation [48,49] or the ratio between separation and compactness [50]; finding density peaks [51] and hybrid solutions [52]; but ultimately the optimal clustering method is highly dependent on the application. In our algorithm, we have implemented a novel clustering method that optimizes a compound image formed by the retina under scrutiny stitched to a reference from healthy retinas with characteristics known a priori, attaining a high sensitivity and specificity of EZ defect area.…”
Section: Discussionmentioning
confidence: 99%
“…If clusters are too few, the algorithm would assign an artificially large area to the EZ defect, and vice versa, if clusters are too many, some pixels in the EZ defect area would be lost. Numerous methods have been proposed to solve this issue, such as evaluation of clustering quality by a validity index [47] based on either the degree of separation [48,49] or the ratio between separation and compactness [50]; finding density peaks [51] and hybrid solutions [52]; but ultimately the optimal clustering method is highly dependent on the application. In our algorithm, we have implemented a novel clustering method that optimizes a compound image formed by the retina under scrutiny stitched to a reference from healthy retinas with characteristics known a priori, attaining a high sensitivity and specificity of EZ defect area.…”
Section: Discussionmentioning
confidence: 99%
“…Min Ren et al found that there was a problem with the improved index by Bensaid et al When c → n, the index will decrease monotonously, approaching 0, lacking the robustness to determine the optimal number of clusters. Therefore, Min Ren et al proposed an improved Xie-Beni index [2] (Xie-Beni index with punitive measures) in 2016 to determine the optimal cluster number. Suneel proposed in 2018 to use diversity to determine the number of clusters [13], in other words, to encourage balanced clustering through cluster size and the distance between clusters.…”
Section: Related Workmentioning
confidence: 99%
“…Clustering analysis has a long history and is a key technology of data analysis. As an unsupervised learning algorithm [1], it does not require prior knowledge and has been widely applied to image processing, business intelligence, network mining, and other fields [2,3]. A clustering algorithm is used to divide data into multiple clusters and make the elements within clusters as similar as possible and the elements between clusters as different as possible.…”
Section: Introductionmentioning
confidence: 99%
“…There are two hyper-parameters that need to be defined to apply SWFC: the fuzzier m and the parameter λ for weights. Most cases reported in the literature suggest that a value of 2.0 for m is a reasonable choice to account for uncertainty (Pal and Bezdek 1995;Ren et al 2016), and m = 2.0 is used in all applications of SWFC discussed in this paper. For parameter λ, there is no rule of thumb guidance in the literature.…”
Section: Illustrative Examplementioning
confidence: 99%